Influence of Bamboo Cellulose Coating on the Flux Performance of Polyvinylidene Fluoride Hollow Fiber Membrane - Perry Law, Nyuk Khui; Rezaur, Rahman; Khairul Anwar, Mohamad Said; Murtala, Namakka; M., Shahabuddin; Muneera S. M., Al-Saleem; Jehan Y., Al-Humaidi; Mohammed M., Rahman; King Kuok, Kuok (North Carolina State University, 2025)
This study showcases the characterization of a surface modified polyvinylidene fluoride (PVDF) hollow fiber membrane via Cellulose/PVDF coating. Scanning electron microscopy shows evidence of Cellulose/PVDF coating where surface roughness and coating lines with cracking is visible. The rough surface correlates with an improved pure water flux. However, the presence of surface cracks and higher cellulose loading results in decreased flux. Fourier transform infrared spectroscopy shows evidence of cellulose on the coated membrane. X-Ray diffraction revealed amorphous phase on the surface of the coated membrane, indicating that coated membrane has improved hydrophilic properties. The coated membrane samples have improved pure water flux performance up to 3 times the value from control (157.8864 L/m2/h/bar) for samples P01 (432.9142 L/m2/h/bar) and P02 (483.8453 L/m2/h/bar) which is the